2018
DOI: 10.1021/acs.macromol.7b02221
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Interaction Parameter for Poly(solketal methacrylate)-block-polystyrene Copolymers

Abstract: A series of symmetric poly­(solketal methacrylate-b-styrene) (PSM-b-PS) copolymers with varying molecular weights that can transform a hydrophobic PSM block to a hydrophilic poly­(glycerol monomethacrylate) (PGM) block through an acid hydrolysis were investigated. This simple chemical transformation significantly enhances the segmental interaction parameter (χ), enabling a phase-mixed block copolymer (BCP) to microphase separate without any additives. Temperature-dependent small-angle X-ray scattering (SAXS) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(69 citation statements)
references
References 47 publications
2
66
1
Order By: Relevance
“… 88 Indeed, the industrial manufacture of GMA monomer is achieved via acid-catalyzed deprotection of IPGMA, 27 and Hoogeveen et al reported the preparation of PGMA-based diblock copolymers from PIPGMA-based precursors via acid hydrolysis at ambient temperature for 72 h. 89 Very recently, Russell and co-workers reported the deprotection of IPGMA residues in a series of polystyrene–PIPGMA (PS–PIPGMA) diblock copolymers using HCl in 1,4-dioxane. 90 Of particular relevance to the present study, a similar strategy was recently utilized by Rimmer and co-workers for the synthesis of sterically stabilized PS–PGMA latexes from precursor core–shell PS–PIPGMA particles. 73 In this case, acid hydrolysis was conducted in aqueous solution at approximately pH 1 for 4–8 h at 60 °C, but no kinetic studies of the extent of deprotection were reported.…”
Section: Resultsmentioning
confidence: 95%
“… 88 Indeed, the industrial manufacture of GMA monomer is achieved via acid-catalyzed deprotection of IPGMA, 27 and Hoogeveen et al reported the preparation of PGMA-based diblock copolymers from PIPGMA-based precursors via acid hydrolysis at ambient temperature for 72 h. 89 Very recently, Russell and co-workers reported the deprotection of IPGMA residues in a series of polystyrene–PIPGMA (PS–PIPGMA) diblock copolymers using HCl in 1,4-dioxane. 90 Of particular relevance to the present study, a similar strategy was recently utilized by Rimmer and co-workers for the synthesis of sterically stabilized PS–PGMA latexes from precursor core–shell PS–PIPGMA particles. 73 In this case, acid hydrolysis was conducted in aqueous solution at approximately pH 1 for 4–8 h at 60 °C, but no kinetic studies of the extent of deprotection were reported.…”
Section: Resultsmentioning
confidence: 95%
“…glyceryl methacrylate. Alternatively, PGOHMA can be prepared by the acid-catalysed hydrolysis of precursor polymers, including poly(solketal methacrylate) [47,48]. Nevertheless, the acidcatalysed hydrolysis of PGMA [23,49] is a less expensive pathway due to the commercial availability of GMA [21].…”
Section: Post-modification Of the Preformed Pgma-based Nanocompositesmentioning
confidence: 99%
“…It has also been reported as a material for ultrafiltration barriers mimicking the natural membranes in kidneys [43]. Poly(isopropylidene glycerol methacrylate), commonly known as poly(solketal methacrylate), is one of those polymers not yet studied widely in the context of block copolymer membranes produced via the SNIPS process [44][45][46][47]. Recently, we reported a detailed comparison of double hydrophobic PS-b-PSMA and amphiphilic PS-b-PGMA diblock copolymer membranes, where the influence of the hydrophobic or hydrophilic nature of the second block was analyzed by water flux and contact angle measurements.…”
Section: Introductionmentioning
confidence: 99%